Dødens variation - Sundby-Sørensen, Merethe (Religionsvidenskabeligt Tidsskrift, 1990)
Aztekisk dødekult og dødeforestillinger The subject is dealt with in the light of Bernadino de Sahagun's extensive source material from the mi-sixteenth century, but in relation to the theoretical discussions and the use of the sources, I refer to previous works: The first argues for a separate land of the dead for children; and the second treats the social and religious importance of women in Aztec society. In the light of interpretations based on analyses of the interaction between the descriptions of ritual and myth, I describe the Aztec lands of the dead: Mictlan, Tlalocan, *Tonacatlan and Ichan tonatiu ilhujcac. Which land of de dead the individual was to reside in depended neither on social position nor on meritorious acts, but only the circumstances of the death, the funeral form and the ritual equipment ensured access to the right environment. Most adults went to Mictlan, children went to *Tonacatlan and people who died in connection with water went to Tlalocan. Ichan tonatiu ilhujcac (the home of the sun in the sky) was reserved for young women and men who died in active battle - for women active battle meant death in childbed and for men death in the heat of war or as victims on the enimies' sacrificial stone. The distance between life and death seems minimal in the Aztec world - the living made use of death and the dead.